Economic planning in France - Timoney, Nicola (Statistical and Social Inquiry Society of Ireland, 1984)
In the nineteen sixties, a number of authors complained of the difficulty of identifying the exact nature of French-style planning. A short historical review of the First to the Sixth Plans (1947-1975) will be followed by a more detailed analysis of the later plans, with particular emphasis on the Ninth Plan prepared for 1984-1988. From a wide variety of possible themes, I have chosen two for detailed consideration. These are: (i) The use of macro-economic models in the planning process, (ii) The question of planning and political consensus. Some analyses of the role of French planning are then presented. Evidence on the implementation of the plans in France precedes our own interpretation of their role.
Read before the Society, 17 April 1984
Keywords: Economic planning; France; 314.15